The Third Leg of Two-legged Lexicography - Tarp, Sven (HERMES - Journal of Language and Communication in Business, 2008)
This article argues that the essence of lexicography is its capacity to satisfy the potential users’ punctual information needs in contrast to their global information needs. Simultaneously it shows that lexicographic theory, which so far has studied only two basic types of social situations where information needs may occur, the communicative and cognitive ones, should also study a third type of basic situations, which are referred to as operational user situations. On this basis, the article projects lexicography beyond the limits of known dictionaries considered as products of applied linguistics and discusses the relation that should be established between lexicography and other branches of human knowledge. It argues that lexicography, focusing on its core specialities, has a lot to contribute to these branches of knowledge. In this respect, it discusses not only traditional dictionaries but also the beneﬁt that authors of handbooks, manuals, how-to’s, user guides, textbooks and other types of texts may have from a renewed lexicographic theory that focuses on quick and easy access to data from which the potential users and readers may retrieve the information needed in speciﬁc situations. Finally, it argues that a number of university study programs may beneﬁt from short courses on the core specialities of lexicography.